Constructing inter-sector practices in mental health for people in psychic suffering - Elisângela Braga de Azevedo; Rafael Nicolau Carvalho; Renata Cavalcanti Cordeiro; Lorena de Farias Pimentel Costa; Priscilla Maria de Castro Silva; Maria de Oliveira Ferreira Filha (Universidade Federal de Santa Maria, 2014)
Doi: 10.5902/2179769213562 Objective: to understand the inter-sector practices of social inclusion developed in the mental health care network to people in psychic suffering, in the municipality of Campina Grande/Paraíba/Brazil. Method: a qualitative, exploratory and descriptive research conducted with four professionals through semi-structured interviews, recorded from June to July 2010. The produced material was analyzed through content analysis, proposed by Bardin. Results: the Psychiatric Reform discourse towards deinstitutionalization, social inclusion and achievement of citizenship has impelled professionals working in substitute services to seek inter-sector partners, such as: National Service for Industrial Training (SENAI), Culture and Living Center, Young Citizen Center and Reference Centers for Social Assistance (CRAS). Conclusion: inclusive practices are effective strategies for psychosocial rehabilitation and contribute to the development of public policies and comprehensiveness of mental health care.